The competing risks of acquiring and being acquired: Evidence from Colombia's financial sector (2010)
This paper studies the determinants of the probability of participating in a process of merging or acquisition for financial institutions in Colombia. We use survival analysis techniques and competing risks models to estimate the probability of participating in such processes as an acquiring or acquired firm. Using an especially rich database containing financial information of Colombian banks for the period 1990-2007, we find that both macroeconomic and microeconomic variables are important determinants of this probability. However, there are differential effects for the acquiring firm and the acquired firm. Particularly, while firm size and solvency are significant determinants of the probability of being an acquiring firm, efficiency is an important determinant of the probability of being acquired. Also, the concentration index, which plays no role for acquiring firms, plays an important role in the probability of being acquired. © Elsevier B.V.